The roles of SARP family regulators involved in secondary metabolism in Streptomyces - Yan, Yusi; Xia, Haiyang (Frontiers in Microbiology, 2024)
Streptomyces species are best known for their ability to produce abundant secondary metabolites with versatile bioactivities and industrial importance. These metabolites are usually biosynthesized through metabolic pathways encoded by cluster-situated genes.These genes are also known as biosynthetic gene clusters (BGCs) of secondary metabolites. The expression of BGCs is intricately controlled by pyramidal transcriptional regulatory cascades, which include various regulators. Streptomyces antibiotic regulatory proteins (SARPs), a genus-specific family of regulators, are widely distributed and play important roles in regulating the biosynthesis of secondary metabolites in Streptomyces. Over the past decade, the biological functions of SARPs have been extensively investigated. Here, we summarized the recent advances in characterizing the roles of SARPs involved in Streptomyces secondary metabolism from the following three aspects. First, the classification and domain organization of SARPs were summarized according to their size variation. Second, we presented a detailed description of the regulatory mechanisms and modes of action of SARPs involved in secondary metabolism. Finally, the biotechnological application of SARPs was illustrated by improving the production of target secondary metabolites and discovering novel bioactive natural products. This review will help researchers to comprehensively understand the roles of SARPs in secondary metabolite biosynthesis in Streptomyces, which will contribute to building a solid foundation for their future application in synthetic biology.